VD_FINDINFO HC / 2012 / 726 vom 12. November 2012 - VD Tribunal cantonal (2012)
FRAIS JUDICIAIRES, DÉPENS, PROCÈS DEVENU SANS OBJET | 106 al. 1 CPC (CH), 107 al. 1 let. e CPC (CH), 241 CPC (CH), 242 CPC (CH)